Incorporating cytologic adequacy assessment into precision oncology workflow using telepathology: An institutional experience. Issue 11 (30th April 2021) - Al Zoughbi, Wael; Kim, David; Alperstein, Susan Ann; Ohara, Kentaro; Manohar, Jyothi; Greco, Noah; Khani, Francesca; Robinson, Brian D.; Rao, Rema A.; Elemento, Olivier; Mosquera, Juan Miguel; Siddiqui, Momin T.
Abstract : Background: Tumor sample quality and quantity determine the success of somatic mutation analysis. Thus, a rapid on‐site evaluation (ROSE) tumor cytology adequacy assessment was incorporated into the workflow of precision oncology at Weill Cornell Medicine in New York City. Optimal samples were obtained from 68 patients with metastatic cancer. Methods: Cytopathologists performed ROSE on fine‐needle aspirate samples via telepathology, and subsequently core‐needle biopsies were obtained. In a retrospective manner, the concordance between adequacy assessment and the success rate of the procedure was evaluated to obtain sufficient tumor tissue for next‐generation sequencing (NGS). Results: Out of the 68 procedures, 43 were documented as adequate and 25 were documented as inadequate. The diagnostic yield of adequate procedures was 100%. Adequacy evaluation predicted the success rate of molecular profiling in 40 of 43 procedures (93%; 95% CI, 80.9‐98.5 procedures). The success rate of molecular testing was significantly higher in the adequate group: 93% compared with 32% in the inadequate group ( P < .0005). Seven procedures that failed to provide quality material for mutational analysis and pathological diagnosis were evaluated as inadequate. Cell block provided sufficient DNA for NGS in 6 cases. In 2 cases, a core biopsy could not be performed; hence, the fine‐needle aspirate material confirmed the diagnosis and was used for NGS testing. Conclusion: These results support the incorporation of ROSE into the workflow of precision oncology to obtain high‐quality tissue samples from metastatic lesions. In addition, NGS testing of concurrent cytology specimens with adequate cellularity can be a surrogate for NGS testing of biopsy specimens. Abstract : Rapid on‐site evaluation (ROSE) of fine‐needle aspirate samples via telepathology predicted the success of molecular profiling of concurrent core‐needle biopsies. Thus, ROSE is an effective protocol that allows for a rapid assessment of the quality of tumor tissue submitted for diagnosis and precision oncology studies.